Factor V Leiden: An Additional Risk Factor for Thrombosis in Protein S Deficient Families? - Koeleman, B P C; Rumpt, D van; Hamulyák, K; Reitsma, P H; Bertina, R M (Thrombosis and Haemostasis, 1995)
We recently reported a high prevalence of the FV Leiden mutation (R506Q, responsible for Activated Protein C resistance) among symptomatic protein C deficient probands (19%), and the involvement of the FV Leiden mutation in the expression of thrombophilia in six protein C deficient families. Here, we report the results of a similar study in protein S deficient probands and families. Among 16 symptomatic protein S deficient probands the prevalence of the FV Leiden mutation was high (38%). This high prevalence is significantly different from that in the normal population, and is probably caused by the selection of probands for familial thrombosis and protein S deficiency. In 4 families, the segregation of the FV Leiden mutation and the protein S deficiency could be studied. In sibships where both abnormalities were segregating, the percentage of symptomatic individuals with both abnormalities was 80%. Three of the seven subjects with only the FV Leiden mutation, and two out of the three subjects with only protein S deficiency had developed thrombosis. These results indicate that in the families presented here the combination of the FV Leiden mutation and the protein S deficiency is associated with a high risk for thrombosis. A reliable estimate of the penetrance of the single defects is not possible, because the number of individuals with a single defect is too low.